2004
DOI: 10.1093/ndt/gfh207
|View full text |Cite
|
Sign up to set email alerts
|

NF- B activation and overexpression of regulated genes in human diabetic nephropathy

Abstract: The activation of NF-kappaB and the transcription of certain pro-inflammatory chemokines in tubular epithelial cells are markers of progressive DN. Proteinuria might be one of the main factors inducing the observed pro-inflammatory phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
263
2
10

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(294 citation statements)
references
References 18 publications
13
263
2
10
Order By: Relevance
“…Experimental and clinical studies have demonstrated that DN exhibits signs of inflammation, such as increased expression of adhesion molecules (44), chemokines (45), growth factors (46), and proinflammatory cytokines, including TNF-␣, in renal tissue (37)(38)(39)(40). In addition, the enhanced passage of proteins across the glomerular barrier as a result of any insult to the filtration compartment exerts deleterious effects on the kidney in part by eliciting an inflammatory reaction with an increased gene expression for several proinflammatory molecules (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and clinical studies have demonstrated that DN exhibits signs of inflammation, such as increased expression of adhesion molecules (44), chemokines (45), growth factors (46), and proinflammatory cytokines, including TNF-␣, in renal tissue (37)(38)(39)(40). In addition, the enhanced passage of proteins across the glomerular barrier as a result of any insult to the filtration compartment exerts deleterious effects on the kidney in part by eliciting an inflammatory reaction with an increased gene expression for several proinflammatory molecules (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…In general, NF-B activates in macrophages and glomerular (including podocytes in proteinuric diseases) and tubular parenchymal cells and correlates with parameters of severity of disease such as proteinuria or inflammation. 59,[61][62][63][64][65] These data have been interpreted as supportive for the role of NF-B in promoting inflammation; however, inflammation itself will promote NF-B activation, and because these data are descriptive, the precise role of the various NF-B complexes in human kidney injury remains uncertain. Functional evidence of NF-B activation has been obtained by transcriptomics-based pathway mapping 66 ; in progressive diabetic nephropathy, there is upregulation of 54 of 138 known NF-B targets with special enrichment in NF-B/IRFF module target genes.…”
Section: Nf-b Activation In Experimental and Human Renal Diseasementioning
confidence: 99%
“…20 -23 Activation of renal NF-B has been described in human kidney diseases, associated to proinflammatory factors overexpression. 24,25 We have now investigated whether CTGF could modulate the inflammatory response in the kidney and the mechanisms underlying this process, evaluating the involvement of the NF-B signaling pathway. …”
mentioning
confidence: 99%